Clinical presentation and early predictors of progression to dilated cardiomyopathy in children with acute myocarditis - Luo, Liu; Huang, Yanyun; Qiao, Xiaoyu; Pang, Yusheng (Frontiers in Pediatrics, 2025)
ObjectiveThe aim of this study was to describe the characteristics and outcomes of acute myocarditis (AM) patients while seeking accessible and valid early predictors for the development of dilated cardiomyopathy (DCM).MethodsWe conducted a retrospective evaluation of 136 consecutive AM patients admitted to our hospital. The patients were categorized into two groups according to their left ventricular ejection fraction (LVEF) at presentation: those with an impaired LVEF of ≤55% and those with a normal LVEF of >55%. Multivariate logistic regression analyses were conducted to identify early predictors of DCM.ResultsThe median age of the study participants was 10.35 years (5.60–14.70), and most of the participants (66.91%) were males. Thirty-eight (27.94%) patients had an LVEF of ≤55%. Compared with those with an LVEF >55%, patients with an LVEF ≤55% presented significantly elevated levels of cardiac troponin I (cTnI) and N-terminal pro-B-type natriuretic peptide (NT-proBNP), as well as more pronounced clinical manifestations, including a greater prevalence of fulminant myocarditis, New York Heart Association (NYHA) class II-IV, abnormal electrocardiogram results, and enlargement of the left ventricle on echocardiography. Univariate analysis revealed that patients with an LVEF of ≤55% had an increased risk of poor outcomes and DCM development. These patients faced the greatest likelihood of death and heart transplantation within the first year following discharge. During short-term follow-up, 15.44% of the children with AM progressed to DCM. According to the multivariable analysis, a higher baseline LV end-diastolic diameter z score (LVEDD z-score) independently predicted this progression (odds ratio [OR], 2.685; 95% confidence interval [CI], 1.232–5.851; P = 0.013).ConclusionsPatients with AM and LVEF ≤55% had a more severe clinical course, higher rates of poor outcomes, and increased risk of DCM progression. Moreover, this subgroup was at the greatest risk for death and heart transplant within the first year post-discharge. During short-term follow-up, 15.44% of the children diagnosed with AM progressed to DCM, with a higher baseline LVEDD z-score identified as a potential early predictor for this progression.